Carbon structure in nanodiamonds elucidated from Raman spectroscopy. (September 2017) - Korepanov, Vitaly I.; Hamaguchi, Hiro-o; Osawa, Eiji; Ermolenkov, Vladimir; Lednev, Igor K.; Etzold, Bastian J.M.; Levinson, Olga; Zousman, Boris; Epperla, Chandra Prakash; Chang, Huan-Cheng
Abstract: Despite their name, nanodiamonds (ND) are comprised of a complex interplay of different carbon phases. The diamond core is surrounded by the shell consisting mostly of disordered sp 3 carbon and graphene-like carbon (GLC). The complex structure makes the characterization of nanodiamonds (ND) a difficult challenge. Recent development of many varieties of NDs for different applications demands quick and reliable characterization of the content of various carbon fragments, as well as the estimation of the diamond core size. In this work, we apply Raman spectroscopy to study the structure of nanodiamonds from different origins, including those produced by detonation (DND), high pressure high temperature synthesis (HPHT), and pulsed laser irradiation (LND). The relative content of GLC, disordered and surface carbon can be easily determined from Raman spectra. In particular, we show how the content of different structure fragments is changed upon de-agglutination, surface oxidation and ion irradiation. We also compare the different ND production methods in terms of the structural uniformity of the nanoparticles. Raman spectroscopy provides unique quantitative tool for ND characterization; we believe that the present data will be useful for understanding the structure of diamond nanoparticles, and will provide the background for obtaining the NDs with desired properties. Graphical abstract: